Assessment of anthropogenic material flows in a circular economy -A case study on zinc used in the construction sector - Persson, Lovisa (My University, 2020)
In the transition to a circular economy, an increased understanding regarding anthropogenic material flows is required in order to advocate towards a sustainable management of materials. The construction sector consumes about one third of all material resources, while generating the largest waste stream in the European Union - thus having a high potential for circularity. The aims of this study are to 1/evaluate the availability of data of anthropogenic flows of zinc in Sweden - a metal of both societal and environmental relevance due to its scale of use, as well as to 2/analyze the assessment to support a transition to a circular economy - with focus on the construction sector. Anthropogenic mass flows of zinc were estimated using Material Flow Analysis along with a review of the literature on assessment of circular economy. This study shows that current data regarding waste flows are not sufficient to estimate flows to waste management and recycling on an elemental level due to low level of detail for aggregated waste flows. Therefore, a complete Material Flow Analysis could not be done. Furthermore, a large focus is being put on waste flows and waste management, i.e. higher recycling rates and an increasing use of secondary raw materials, however with low attention paid to the qualitative aspects of recycling. The understanding, quantification and estimation of anthropogenic flows of materials through the economy provides an important knowledge base when deciding on measures and policy instruments related to circular economy. Recycling is important to reduce the demand for virgin raw materials. However, the initial material and energy resources used to build a construction are for the most part lost through recycling - a transition to a circular economy, therefore requires measures beyond efficient recycling.
Keywords: circular economy, resource efficiency, material flow analysis, zinc, construction sector, reuse, recycling.